Alterations of structure and functional connectivity of visual brain network in patients with freezing of gait in Parkinson’s disease - Gan, Lu; Yan, Rui; Su, Dongning; Liu, Zhu; Miao, Guozhen; Wang, Zhan; Wang, Xuemei; Ma, Huizi; Bai, Yutong; Zhou, Junhong; Feng, Tao (Frontiers in Aging Neuroscience, 2022)
Freezing of gait (FOG) is a disabling gait disorder common in advanced stage of Parkinson’s disease (PD). The gait performance of PD-FOG patients is closely linked with visual processing. Here, we aimed to investigate the structural and functional change of visual network in PD-FOG patients. Seventy-eight PD patients (25 with FOG, 53 without FOG) and 29 healthy controls (HCs) were included. All the participants underwent structural 3D T1-weighted magnetic resonance imaging (MRI) and resting state functional MRI scan. Our results demonstrated a significant decrease of right superior occipital gyrus grey matter density in PD-FOG relative to non-FOG (NFOG) patients and healthy controls (PD-FOG vs PD-NFOG: 0.33±0.04 vs 0.37±0.05, p=0.005; PD-FOG vs HC: 0.37±0.05 vs 0.39±0.06, p=0.002). Functional MRI revealed a significant decrease of connectivity between right superior occipital gyrus and right paracentral lobule in PD-FOG compared to PD-NFOG (p=0.045). In addition, the connectivity strength was positively correlated with grey matter density of right superior occipital gyrus (r=0.471, p=0.027) and negatively associated with freezing of gait questionnaire (FOGQ) score (r=-0.562, p=0.004). Our study suggests that the structural and functional impairment of visual-motor network might underlie the neural mechanism of FOG in PD.